Effect of estradiol and predator cues on behavior and brain responses of captive female house sparrows (Passer domesticus) - Kimball, Melanie G.; Harding, Courtney T.; Couvillion, Kaitlin E.; Stansberry, Keegan R.; Kelly, Tosha R.; Lattin, Christine R. (Frontiers in Physiology, 2023)
The presence of predators can cause major changes in animal behavior, but how this interacts with hormonal state and brain activity is poorly understood. We gave female house sparrows (Passer domesticus) in post-molt condition an estradiol (n=17) or empty implant (n=16) for one week. Four weeks after implant removal, a time when female sparrows show large differences in neuronal activity to conspecific vs. heterospecific song, we exposed birds to either 30 min of conspecific song or predator calls, and video recorded their behavior. Females were then euthanized, and we examined neuronal activity using the expression of the immediate early gene (IEG) ZENK to identify how the acoustic stimuli affected neuronal activation. We predicted that if female sparrows with estradiol implants reduce neuronal activity in response to predator calls as they do to neutral tones and non-predatory heterospecifics, they would show less fear behavior and a decreased ZENK response in brain regions involved in auditory (e.g., caudomedial mesopallium) and threat perception functions (e.g., medial ventral arcopallium) compared to controls. Conversely, we predicted that if females maintain auditory and/or brain sensitivity towards predator calls, then female sparrows exposed to estradiol would not show any differences in ZENK response regardless of playback type. We found that female sparrows were less active during predator playbacks independent of hormone treatment and spent more time feeding during conspecific playback if they had previously been exposed to estradiol. We observed no effect of hormone or sound treatment on ZENK response in any region of interest. Our results suggest that female songbirds maintain vigilance towards predators even when in breeding condition.